Utility of Alternative Effect Size Statistics and the Development of a Web-Based Calculator: Shiny-AESC - Zhang, Don C. (Frontiers in Psychology, 2018)
Alternative displays of effect size statistics can enhance the understandability and impact of validity evidence in a variety of applied settings. Arguably, the proliferation of alternative effect size statistics has been limited due to the lack of user-friendly tools to create them. Common statistical packages do not readily produce these alternative effect sizes and existing tools are outdated and inaccessible. In this paper, I introduce a free-to-use web-based calculator (https://dczhang.shinyapps.io/expectancyApp/) for generating alternative effect size displays from empirical data. This calculator requires no mathematical or programming expertise, and therefore, is ideal for academics and practitioners. I also present results from an empirical study that demonstrates the benefits of alternative effect size displays for enhancing lay people’s perceived understandability of validity information and attitudes toward the use of standardized testing for college admissions.